Memaknai Kain Poleng Sebagai Inspirasi Penciptaan Karya Seni Lukis - Putra, I Kadek Sangging Adi Apreliana; Utami, Ni Made Purnami; Gulendra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
The author's interest stems from the visual uniqueness of Poleng cloth which influenced the writer in adopting Poleng cloth as a painting. So it occurred to the author's desire to create a painting with the concept of Poleng Cloth as an inspiration for the creation of a painting that could represent the theme raised. The problem faced is how to visualize Poleng cloth to represent ideas, phenomena, meanings and techniques presented in creating works of art. The method of creation is a way of creating works of art systematically. In realizing this creation, the methods used are: the stages of exploration (exploration), imprivisation (experimentation), and forming (formation), which are supported by elements of fine art so that 6 works are created entitled: 1) "contemplation", 2 ) "Thennow", 3) "Related", 4) "Alignment", 5) "Heritage", 6) "Poleng establishes togetherness". In creating works, the author applies several artist references related to technique, color, composition, and tools, so that they can be developed to produce works with the development of several techniques with polleng cloth objects, it is expected to produce the author's identity in painting works. From this creation, the authors develop ideas creatively to become works that have aesthetic value and are meaningful. And with the creation of this work, the meaning and phenomenon presented by the author in the creation of the work can be conveyed.